Cut effects simulating grazing on the chemical composition of grains of winter cereals - Duca, Leo de Jesus Antunes Del; Guarienti, Eliana Maria; Fontaneli, Renato Serena; Zanotto, Dirceu Luis (Pesquisa Agropecuaria Brasileira, 1999)
An increased demand for activities integrating crop-cattle production in the Rio Grande do Sul plateau has contributed to a dual purpose use (forage and grain) of winter small grains. Therefore, a better knowledge on how to use these cereals for pasture, as well as on the economic value of grains and their potential use in human and animal foods, is necessary. The objective of this study was to evaluate the influence of cuts (one and two) simulating cattle grazing in the chemical composition of the grain of white oats (UPF 14), black oats Avena strigosa (comum), rye (BR 1), triticale (BR 4), barley (BR 2), and wheat (IPF 55204 and PF 87451). In the cereal average, cuts did not affect the values of crude fiber, fat, crude energy, and ureatic activity and led to increased levels of ash with two cuts. Excepting black oats and barley, an increase in crude protein percentuals with the cuts was observed. Nevertheless, a reduction in non-nitrogeneous substances was observed in the cereal average, with the cuts. These results suggest the possibility of using the winter cereals for dual purpose, using the grains without greater damages in their chemical composition.